Does anti-competitive regulation matter for productivity? Evidence from European firms - Jens Matthias Arnold; Giuseppe Nicoletti; Stefano Scarpetta (Institute for the Study of Labor (IZA), 2011)
Using firm-level data for a sample of European countries, we focus on the effects that product-market regulations have on firm-level TFP growth. We proxy regulatory burdens using the OECD indicators of sectoral non-manufacturing regulations. These allow accounting for both the direct effects of sectoral regulation on within-sector performance and the indirect effects of sectoral regulation on firms in other sectors through intersectoral input-output linkages. Our econometric specification of TFP is based on a neo-Schumpeterian empirical specification in which productivity improvements depend on growth at the global technological frontier and a catch up term. We assume that regulation can affect productivity growth both directly and by slowing down the rate of catch up. We find that product market regulations that curb competitive pressures tend to reduce the productivity performance of firms. The negative effect is particularly strong on firms characterised by an above-average productivity growth. Domestic regulations that affect all regulated firms in the same way seem to be more important than border regulations in this context.
urn:nbn:de:101:1-201104113848
Keywords: D24; L11; L51; 330; total factor productivity; firm-level data; product market regulation; Regulierung; Produktivität; Wirtschaftswachstum; Schätzung; Europa